2012
DOI: 10.1080/09670262.2012.692816
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of carotenoids and regulation of the carotenoid biosynthesis pathway in response to high light stress in the unicellular microalga Chlamydomonas reinhardtii

Abstract: The carotenoid biosynthesis pathway catalyses the synthesis of essential pigments that are crucial for light harvesting and photoprotection in photosynthetic organisms. It allows the production of several commercially important compounds and is the target of many herbicides. In the present work we studied the influence of light on the carotenoid composition and the expression of genes encoding the main steps of the pathway in the freshwater microalga Chlamydomonas reinhardtii. We observed that there is an acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(35 citation statements)
references
References 49 publications
2
30
0
Order By: Relevance
“…3b). This may be attributed to the synthesis of xanthophylls under stressful conditions that contribute to the activation of the xanthophyll cycle to dissipate surplus absorbed light energy as heat, rendering the microalgae less prone to photo-oxidative damage (Couso et al 2012;Wykoff et al 1998). Our results also show that the Car/Chl ratio is positively related to starch content and inversely related to F v /F m (Figs.…”
Section: Discussionsupporting
confidence: 70%
“…3b). This may be attributed to the synthesis of xanthophylls under stressful conditions that contribute to the activation of the xanthophyll cycle to dissipate surplus absorbed light energy as heat, rendering the microalgae less prone to photo-oxidative damage (Couso et al 2012;Wykoff et al 1998). Our results also show that the Car/Chl ratio is positively related to starch content and inversely related to F v /F m (Figs.…”
Section: Discussionsupporting
confidence: 70%
“…In the red stage, cells were wrinkled, and the cell wall was abridged (Figure 2b). It has been reported that the synthesis of carotenoids was subject to detrimental conditions, such as high light intensity, nutrient starvation or other stress conditions [20]. Thus, it was inferred that the red cell might have been under stress.…”
Section: Morphology Analysismentioning
confidence: 99%
“…In order to estimate the growth of microalgae, the dry cell weight (DCW) was measured according to Couso et al [20]. Microalgae were cultured to the log phase of growth in flasks, then 50 mL cell cultures were transferred to glass columns (4.1 cm in diameter, 37 cm in height), and diluted with 250 mL of F medium with different concentrations of NaNO 3 (0.075, 0.15, 0.3, 0.6 and 0.9 g/L) to ensure the OD 680 of initial culture was approximate 0.2.…”
Section: Effects Of Initial Nano 3 Concentration On Microalgae Growthmentioning
confidence: 99%
“…In Chlamydomonas this response to high light shifts is well documented [4]. The synthesis of zeaxanthin in Chlamydomonas cells after exposure to a high light stress [35] and other kind of stress conditions [36] has been previously reported. It has been demonstrated that this zeaxanthin is produced from violaxanthin via the xanthophyll cycle [33], but neither the enzyme nor the gene encoding this putative violaxanthin de-epoxidase (VDE) has been identified yet in Chlamydomonas.…”
Section: Screening Of Insertional Mutants With An Altered Response Tomentioning
confidence: 92%